Transformasi Kebijakan Pengendalian dan Pemantauan Risiko dalam Navigasi Bank Indonesia Selama Kurun Waktu 5 Tahun Terakhir - Ainur Oktania; Dwi Silfani; Noubel Putra Nainggolan; Hasyim Hasyim (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
This research focuses on the transformation of risk control and monitoring policies conducted by Bank Indonesia over the past five years (2018-2023). It uses qualitative analysis methods to examine the evolution of Bank Indonesia's policies through publications of financial institutions such as Bank Indonesia, OJK, and BPK. This study shows that policy impact evaluation plays an important role in identifying areas of improvement and new solutions to enhance policy effectiveness. Bank Indonesia adjusts strategies responsively and proactively to keep up with financial market dynamics and technological developments, and integrates the principles of international standards in banking supervision and risk management. Synchronizing policies with international standards is a top priority for maintaining the credibility of global markets. In facing the challenges of global economic change, technological innovation, and dynamic regulations, Bank Indonesia is committed to conducting in-depth reviews and policy adjustments to face the future. The evolving approach allows Bank Indonesia to strengthen its role in maintaining financial system stability and promoting sustainable economic growth. This research provides insights into Bank Indonesia's successes and challenges in transforming its risk control and monitoring policies.